The optical properties of Mg-doped ZnO quantum dots. (15th July 2022) - Wu, Wei-Che; Juang, Yung-Der
Abstract: This research found that ZnO doping with Mg 2+ can control its fluorescent intensity, energy gap and fluorescent wavelength. The non-high temperature manufacturing process (50 °C) can also avoid the reduction of fluorescent efficiency to a certain extent. A simple sol-gel method is used to prepare a transparent Zn1-X MgX O quantum dot solution, and the product is precipitated by a direct precipitation method. After purification, the Zn1-X MgX O quantum dot powder are obtained, which can be re-dissolved into the solution. The results show that the doping of Mg 2+ in ZnO led to the increase of fluorescent intensity and energy gap. Also, with the increase of doping ratios, the PL intensity increases and the emission bands are slightly blue-shifted. Graphical abstract: Image 1 Highlights: ˙ A simple sol-gel method is used to prepare a transparent and stable Zn1-X MgX O quantum dot solution. ˙ The doping of Mg 2+ in ZnO leads to the decrease in grain size. ˙ The doping of Mg 2+ in ZnO leads to the increase of fluorescent intensity and energy gap. Also, there is a phenomenon of blue shift observed in the fluorescent spectra.